James Joyce and the politics of egoism - Rabaté, Jean-Michel, 1949- (Cambridge University Press, 2001)
In James Joyce and the politics of egoism a leading scholar approaches the entire Joycean canon through the concept of "egoism". This concept, Jean-Michel Rabaté argues, runs throughout Joyce's work, and involves and incorporates its opposite, "hospitality", a term Rabaté understands as meaning an ethical and linguistic opening to "the other". Rabaté explores Joyce's complex negotiation between these two poles in a study of interest to all scholars of modernism.